The Critical Raw Materials Issue between Scarcity, Supply Risk, and Unique Properties - Girtan, Mihaela (Materials (Basel), 2021)
This editorial reports on a thorough analysis of the abundance and scarcity distribution of chemical elements and the minerals they form in the Earth, Sun, and Universe in connection with their number of neutrons and binding energy per nucleon. On one hand, understanding the elements’ formation and their specific properties related to their electronic and nucleonic structure may lead to understanding whether future solutions to replace certain elements or materials for specific technical applications are realistic. On the other hand, finding solutions to the critical availability of some of these elements is an urgent need. Even the analysis of the availability of scarce minerals from European Union sources leads to the suggestion that a wide-ranging approach is essential. These two fundamental assumptions represent also the logical approach that led the European Commission to ask for a multi-disciplinary effort from the scientific community to tackle the challenge of Critical Raw Materials. This editorial is also the story of one of the first fulcrum around which a wide network of material scientists gathered thanks to the support of the funding organization for research and innovation networks, COST (European Cooperation in Science and Technology).